The Tehran Older Adults' Leisure Time and Physical Activity With Emphesize of Sport Equipments Provided by Municipality in 2010 - Mahboubeh Chamanpira; Aboulfazl Farahani; Majed Jalali Farahani (University of Social Welfare & Rehabilitation Sciences, 2014)
Objectives: The purpose of this research is to evaluate the quality of the older adults’ leisure time in Tehran focused on their physical activity and their satisfaction with outdoor sport facilities provided in the parks by municipality. Methods & Materials: The type of research is descriptive in which Tehran is divided into 5 (geographical) districts. Through cluster sampling method, 366 individuals has been randomly selected out of 701300 people as Tehran elderly population. The information gathering tool is a questionnaire made by the researcher. Its validity and reliability was measured by experts and Cronbach’s alpha 0.80. Pearson’s r correlations were conducted in order to determine whether significant correlations exist between variables. All statistical analysis were done using SPSS 13 software and alpha level was set at <0.05 Results: findings show that about 74% of the elderly do exercise, most of which is walking. It has been revealed through this research that 59.7% are moderate with the quality of their leisure time. In addition, 48.2% does not use the sports equipments in the parks and 41.7% think that body-building equipment in the parks highly or absolutely highly appropriate for the elderly. There is a meaningful correlation between age and duration of leisure time (P<0.01).Whereas, the correlation between age and satisfaction with facilities is not meaningful (P≤0.05). Furthermore, there are also meaningful correlation between gender and the degree of satisfaction. Conclusion: According to findings of this research, the majority of elder were satisfied with their liesure time at moderately level. Doing physical activity have a significant role in their satisfaction of leisure time. Existing of appropriate sports equipments in parks encourage them to practice physical activities. As a result, the extension and development of these facilities are recommended.